Supernumerary Teeth Adjacent to Fully Erupted Third Molars in all four Quadrants: A Case Report - Vudata Kiran; Vudata Nandan (International Journal of Scientific Research in Dental and Medical Sciences (IJSRDMS), 2024)
Supernumerary teeth are formed due to disturbances during the developmental stages of a tooth. The prevalence of supernumerary teeth is higher in the maxilla than the mandible and shows a predilection for the male gender. They may also demonstrate a familial tendency. Such teeth may lead to complications like impaction/altering the eruption path of adjacent teeth, as well as an increased risk of pathologies. Management of these extra teeth is mandated as and when they have been screened, identified, and noted to damage the adjacent teeth or other dentoalveolar structures. This case report presents an extremely rare case of distomolars in all four quadrants in a non-syndromic patient with no positive familial history.